Trastuzumab: Updated Mechanisms of Action and Resistance in Breast Cancer - Claret, Francois X.; Vu, Thuy T. (Frontiers in Oncology, 2012)
HER2-positive breast cancer accounts for 20–30% of all breast cancers and has the second-poorest prognosis among breast cancer subtypes. The approval of trastuzumab in 1998 has significantly improved patients’ outcomes and paved the way for the beginning of advent of targeted approaches in breast cancer treatment. However, primary or acquired resistance to trastuzumab has been increasingly recognized as a major obstacle in the clinical management of this disease. In addition, in clinical practice, there are currently no conclusive biomarkers for patient response to trastuzumab. Therefore, understanding the molecular mechanism of trastuzumab and the development of resistance to this drug are of interest. Such understanding will provide the guidance critically needed for the design of better combination therapy and will allow the appropriate selection of patients who are responsive to trastuzumab-based strategies. In line with that, our review highlights the well-accepted mechanisms of action and resistance to the therapy and discusses the progress that has been made toward successfully overcoming this resistance.